Development of Project-Based Teaching Modules to Improve Fine Motor Skills of Early Childhood - Yulianasari, Nova; Sukiman (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Educators have difficulty finding learning device guides that are easy to apply and can be modified. In fact, the ability of educators to organize learning activities and learning devices that suit children's needs is very important, in order to support the optimization of every aspect of development in early childhood. This study aims to develop a project-based teaching module to improve fine motor skills in early childhood. The research method is Research & Development with the ADDIE model ( Analysis, Design, Development, Implementation, Evaluation ). Validation was carried out by three expert lecturers and two teachers as justification when field validation was carried out. Data collection techniques used interviews, questionnaires, and observations. Data analysis the need for a preliminary study of teacher interview data was analyzed descriptively narratively, and validated with the results of observations of classroom learning activities and the results of the questionnaire of parents using the Likert method on a scale of 1-4. Qualitative data in the form of input, criticism, and suggestions put forward by media experts, material experts, and teachers to improve the product. Quantitative data was obtained from the answers to the questionnaire which were then converted into qualitative data by giving a score using a Likert scale to assess the feasibility of the teaching module according to the assessment criteria. The results of the feasibility test of the teaching module from material experts showed a value of 4.48 with good criteria, from the results of the teacher and parent questionnaires for the effectiveness of the value of 90.16 with very good criteria. Based on the results of this study, it has produced a project-based teaching module that is effective in developing the fine motor aspects of early childhood.